ONE APPROACH TO THE ANALYSIS OF PHRASES IN PRIMARY SCHOOLS - Марија M. Тир Борља (Faculty of Philosophy, University of Novi Sad, City Library of Pančevo, 2012)
This paper deals with phrases in Serbian language teaching in primary schools. First, the level of presence and study of phrases in Serbian language teaching in the primary school curriculum is considered. Then, on the basis of insights into contemporary linguistic and didactic-methodical literature and personal inquiries in direct classroom practice, a concrete methodical elaboration and model for analyzing the contents of the phrase has been created. The focus of the paper is the methodical elaboration that can allow pupils to be more active and better at understanding the syntagmatic issues in the teaching process.